THE RULE OF HEADMASTER IN IMPROVING TEACHER PEDAGOGY COMPETENCE AT SMPS ASSALAMIYAH OMBEN - Fadli, Marsuki; Ifadhah, Hurriyatul; Nurhadi, Ali (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
In the education process changes will continue, both scientifically and planned changes, in accordance with the capabilities and wishes of the school. The headmaster is one of the drivers of positive and significant change in education. It can be shown that there are many quality schools because they are led by headmaster who are able to guide and provide direction to the teacher council. The headmaster is leader has an important role in improving teacher competence. The ability of the headmaster to foster and assist teacher competence with the aim that teachers can solve problems properly and carry out their duties properly and efficiently. So on this season the researcher want to find out how is the role of the headmaster in improving teacher pedagogic competence, and what are the obstacle factors and supporting factors for headmaster in improving teacher pedagogic competence at Smps Assalamiyah Ombenl